Data-mining Based Expert Platform for the Spectral Inspection. Issue Volume 10:Issue S306(2014) (1st July 2015) - Tian, Haijun; Xu, Yang; Tu, Yang; Zhang, Yanxia; Zhao, Yongheng; Lei, Guohong; He, Boliang; Cui, Chenzhou; Chen, Xuelei
Abstract: We propose and preliminarily implement a data-mining based platform to assist experts to inspect the increasing amount of spectra with low signal to noise ratio (SNR) generated by large sky surveys. The platform includes three layers: data-mining layer, data-node layer and expert layer. It is similar to the GalaxyZoo project and it is VO-compatible. The preliminary experiment suggests that this platform can play an effective role in managing the spectra and assisting the experts to inspect a large number of spectra with low SNR.